THE MYSTIFICATION OF DRUG ABUSE AS A COPING MECHANISM FOR BURN OUT STRES - Heada Auzani Aufar Lambertus; Lucky Nurhadiyanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the phenomenon of the mystification of substance abuse—including narcotics, psychotropics, and other addictive substances as a maladaptive coping strategy for work-related stress among office employees. High workloads, psychosocial pressures, and insufficient workplace support contribute to chronic stress, prompting individuals to seek immediate relief through substance use. Utilizing a qualitative research design, data were collected through in-depth interviews with three former Drug users, a psychologist, and an inpatient supervisor at the National Narcotics Board (BNN) Rehabilitation Center in Lido, Indonesia. The findings reveal that drug use is not solely driven by recreational motives, but rather functions as a dysfunctional coping mechanism, often rationalized as a means to enhance productivity or alleviate fatigue. Both internal factors, such as emotional exhaustion, and external factors, including workplace demands and social influences, interact in shaping substance use behaviors. The study underscores the need for comprehensive employment policies promoting work-life balance, accessible psychological support services, and preventive education on the risks of substance abuse within occupational settings.